Targeted DNA methylation profiling reveals epigenetic signatures in peanut allergy - Zhou, Xiaoying; Han, Xiaorui; Lyu, Shu-Chen; Bunning, Bryan; Kost, Laurie; Chang, Iris; Cao, Shu; Sampath, Vanitha; Nadeau, Kari C. (JCI insight, 2021)
DNA methylation (DNAm) has been shown to play a role in mediating food allergy; however, the mechanism by which it does so is poorly understood. In this study, we used targeted next-generation bisulfite sequencing to evaluate DNAm levels in 125 targeted highly informative genomic regions containing 602 CpG sites on 70 immune-related genes to understand whether DNAm can differentiate peanut allergy (PA) versus nonallergy (NA). We found PA-associated DNAm signatures associated with 12 genes (7 potentially novel to food allergy, 3 associated with Th1/Th2, and 2 associated with innate immunity), as well as DNAm signature combinations with superior diagnostic potential compared with serum peanut-specific IgE for PA versus NA. Furthermore, we found that, following peanut protein stimulation, peripheral blood mononuclear cell (PBMCs) from PA participants showed increased production of cognate cytokines compared with NA participants. The varying responses between PA and NA participants may be associated with the interaction between the modification of DNAm and the interference of environment. Using Euclidean distance analysis, we found that the distances of methylation profile comprising 12 DNAm signatures between PA and NA pairs in monozygotic (MZ) twins were smaller than those in randomly paired genetically unrelated individuals, suggesting that PA-related DNAm signatures may be associated with genetic factors.